ARAHAN PENGENDALIAN BENCANA BANJIR BERBASIS SPASIAL DI KECAMATAN CENRANA, KABUPATEN BONE - Luthfi, Muhammad; K., Risnawati; Usman, Khairul Sani (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
Floods are natural events that occur in areas with high river discharge. This research focuses on seasonal flooding events in Cenrana Sub-district triggered by high rainfall and flooding in the upper reaches of the Walannae River in Wajo Regency. Factors such as slope, elevation, soil type and land use are thought to influence flooding. In addition to physical aspects, vulnerability factors including physical, social and economic vulnerability also play a role in the impact of post-flood disasters. The research methodology used Weighted Overlay analysis based on vulnerability parameters through scoring method to assess the level of flood risk and qualitative descriptive analysis method for control measures in Cenrana Sub-district. The results showed a low flood risk area of 41.55 km2, a medium risk area of 76.65 km2, and a high risk area of 25.25 km2. Disaster control strategies must consider the risk classification of the affected area, where high-risk areas require building regulation policies along rivers and seas, integrated disaster insurance, and medium-risk areas that require irrigation and drainage systems, as well as disaster education for residents. This research provides valuable insights for local governments in formulating flood disaster management policies and serves as a reference for studying risk mapping in the future.